Combustion characteristics, performance and emissions of a diesel engine fuelled with water/diesel emulsions (2015)
ABSTRACT: The impact of two different formulations of water-in-diesel emulsions (WDE1 and WDE2) and diesel fuel containing 10 % of palm oil biodiesel (B10) on the combustion characteristics, performance and pollutant emissions of an automotive diesel engine was evaluated at 1,800 rpm and two different torque levels (66 Nm and 99 Nm). Both emulsions exhibited longer ignition delays, in comparison with B10. The premixed combustion phase was drastically increased while the diffusive combustion phase was reduced, and the combustion duration remained almost invariable respect to B10 fuel. Combustion efficiency, determined through the ratio between cumulative heat release rate and lower heating value was slightly deteriorated at low torque however an improvement was observed at 99 Nm. On the other hand, bulk in cylinder temperature showed a strong dependence on emulsion formulation and operating conditions, exhibiting a decrease at low load due to the heat of vaporization of water contained in the emulsions. Higher brake specific fuel consumptions (BSFC) and equivalence ratios were obtained with both emulsions due to their lower heating value compared to B10. CO and THC emissions increased in comparison to B10. On the other hand, NOx emissions were decreased at both engine-operating modes reaching a reduction up to 40 % with the WDE1 emulsion while particulate matter emissions were highly water content dependent WDE1 and reached reductions up to 11 % respect to B10 for WDE1. From this experimental work, it was concluded that depending on engine operating mode and water content, the water in diesel emulsions are efficient fuels, which can be directly used in conventional diesel engines showing a potential to reduce simultaneously NOx emissions and particulate matter. More research work is being carried out at this extent in order to assess the impact of the optimum water-in diesel emulsion on engine durability, non-regulated emissions and particle matter biologic activity.